Mechanical Properties and Failure Mode of Proximal Screw Fixation Technique Using Locking Compression Plate for Proximal Interphalangeal Arthrodesis in Horses: An Ex Vivo Study - de Souza, Anderson F.; Pereira, César A.M.; Costa, Claudio; Fürst, Anton; Kümmerle, Jan M.; De Zoppa, André L.V. (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objective The aim of this study was to measure the mechanical properties and failure mode of an ex vivo model of proximal interphalangeal arthrodesis in horses with different methods of proximal screw fixation using a locking compression plate.Study Design Pastern joint arthrodesis with a 3-hole 4.5-mm narrow locking compression plate was performed on 20 forelimbs of equine cadavers, randomized into four groups based on the fixation method and type of proximal screw used: unicortical cortex, bicortical cortex, unicortical locking, bicortical locking. Single-cycle axial compression testing was conducted until failure. The frequency of implant plastic deformation was recorded. Bone failure analysis was performed through computed tomography examinations and fractal analysis.Results There were no differences in the analysed mechanical variables and fractal dimension among the groups. Transarticular screws showed a higher frequency of deformation (75%) regardless of the group. Both unicortical locking and bicortical locking groups deformed the plate more frequently.Conclusion The type of screw used in the proximal hole of the locking compression plate and its method of anchoring in the proximal phalanx do not affect the mechanical properties of pastern arthrodesis in equine cadavers subjected to single-cycle axial compression tests until failure.
Keywords: unicortical screw; stress riser; pastern joint; horse; locking compression plate; arthrodesis